Reevaluating constitutional liability: Russian and international perspectives - Vinogradov, Vadim (Revista de Investigações Constitucionais, 2022)
While a comprehensive research and literature exists on legal responsibility, the nature of constitutional liability is much less explored. Constitutional liability is a crucial tool for strengthening and development of democracy. In practice, not all countries have a direct constitutional and legislative establishment of constitutional liability as a special form of legal responsibility. For example, Russia has its own way of determining constitutional liability, which can serve as grounds for thought provoking reflection in other legal systems. In this article, the author will consider the constitutional liability as a form of legal responsibility, address the questions of interrelation between constitutional liability and other forms of legal responsibility, as well as explore the grounds of constitutional liability by comparing constitutions, a number of various laws, some subordinate legislative acts of Russia and about fifteen other countries. Such analysis allows one to draw conclusions that bring some novelty, newness into the field of public law as a whole.